2008
DOI: 10.21307/ijssis-2017-327
|View full text |Cite
|
Sign up to set email alerts
|

Training Data Compression Algorithms and Reliability in Large Wireless Sensor Networks

Abstract: With the availability of low-cost sensor nodes there have been many standards developed to integrate and network these nodes to form a reliable network allowing many different types of hardware vendors to coexist. Most of these solutions however have aimed at industry-specific interoperability but not the size of the sensor network and the large amount of data which is collected in course of its lifetime. In this paper we use well studied data compression algorithms which optimize on bringing down the data red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…A comparison metric (Iyer et al, 2008g) is used by classification algorithms let it be similarity based or discriminative model. In a probability model or when learning weights are in a neural network, the total sum of probabilities must be equal to 1.…”
Section: Similarities and Dissimilaritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison metric (Iyer et al, 2008g) is used by classification algorithms let it be similarity based or discriminative model. In a probability model or when learning weights are in a neural network, the total sum of probabilities must be equal to 1.…”
Section: Similarities and Dissimilaritiesmentioning
confidence: 99%
“…A OMNET mobility framework simulator, using interference modeling as derived in Section IV and Table 9.3. We use two models to analyze the data collected from the mobility simulator, one uses the covariance technique (Kumar et al, 2008), (Iyer et al, 2008g) to optimize as shown in equation (9.12), when not too much of co-channel interference is seen. The second (Duda et al, 2000), which de-correlates under the presence of heavy co-channel interference.…”
Section: Mobility and Cognitive Radio Sub-channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limited number of publications on the topic [Iyer et al 2008;Marco and Neuho↵ 2004], there is clearly significant scope for future work in this area.…”
Section: Open Research Issues and Future Directionsmentioning
confidence: 99%
“…The calibration experiment was performed on a real IRB120 robot as shown in Figure 3. The locations of laser spot at both PSDs were wirelessly [20,21] transferred to the computer.…”
Section: Calibration With Precise Data In Simulationmentioning
confidence: 99%